Exiled Poetics: Glück, Darwish, and A Transnational Edenic Imagination - Davis, Megan (Art/Research International)

(untitled) (University of Alberta, 2022)
Taking up the writings of Louise Glück and Mahmoud Darwish, this essay (re)searches the place and potential of a transnational, Edenic imagination as a vision of belonging amidst the alienation of modern life. Where a transnational poetics rejects ossified borders and boundaries, seeking porosity and imaginative possibilities that work across, around, through, and in-between, an Edenic imagination embraces a consciousness that simultaneously holds holy memory alongside longing for transcendence; so too do these ways of reading and seeing refract in the art-making I attempt as I seek the invisible web of connective, human tissue present in the poetic renderings of Eden by Glück and Darwish. As forces of modernity, colonization, and globalization maim and sever, a transnational, Edenic imagination gives language and location to our thirst for sacred inhabitance. As a method of inquiry, such a reading invites both researcher and reader to dwell in the liminal space of poetics.Guided by the poetic explorations of Eden and exile by Glück and Darwish, I work to consider how poetry itself becomes a hybrid site of belonging. The hope is that, through a deep (re)reading of the verses in which Glück and Darwish employ Eden as a metaphor, poetic inquiry might provide a way for us to more fully traverse categories of life, death, time, longing, space, and culture, exploring the complex matrices of our human experience and pursuit of home.